Bioatividades de frações dos extratos de Lentinula edodes e Pleurotus sajor-caju em cultivo de células de mamíferos - Finimundy, Tiane Cristine (My University, 2018)
Mushrooms have vast prospects as sources of medicinal properties, since they have been used since ancient times to treat diseases and promote health in general. They have a number of interesting bioactive compounds which aroused the interest of the scientific area. The present study aims to evaluate the bioactive properties and the chemical and nutritional composition of the Pleurotus sajor-caju and Lentinula edodes mushrooms. The antioxidant activity of the extract was evaluated through DPPH, reducing power, TBARS and beta carotene assays. Antitumor activity was performed on NCI-H460, HepG2, HeLa, MCF-7, PLP2, HCT-116 and MRC-5 cells, and anti-inflammatory for the ethanolic extract of P. sajor-caju on Raw 264.7. The composition of the P. sajor caju sample in tocopherols was determined by High Performance Liquid Chromatography (HPLC) coupled to a fluorescence detector (DAD). The fatty acid and sugar profiles were obtained by gas chromatography coupled to a flame ionization detector (GC-FID) and by HPLC coupled to a refractive index detector (RID). P. sajor-caju showed to be an important source of antioxidants mainly phenols (147.54 μg / g) and tocopherols (615.9g / 100g). β-tocopherol was the form found in higher amounts. This extract showed antioxidant activity, which is more significant for lipid peroxidation inhibition assays (EC 50 values below 2.6 mg / mL). Macronutrient profile determination showed high levels of protein (17.29 g / 100 g) and carbohydrates (76.18 g / 100 g), presenting low lipid values (1.16 g / 100 g). Analysis of the composition of fatty acids led to the quantification of 22 molecules, with predominance of polyunsaturated fatty acids, particularly oleic and linoleic acids, 17-61% and 20-54%, respectively. The flow cytometry assay was used to verify the type of induced death for both mushrooms, which showed similar results, indicating death by apoptosis. The studies carried out describe the nutraceutical potential of the analyzed species, as well as the molecular docking makes us think of a possible pro-apoptotic and anti-inflammatory activity. The consumption of mushrooms in nature as in extracts can have a beneficial effect on health and help in the treatment of certain diseases.
Os cogumelos têm vastas perspectivas como fontes de propriedades medicinais, pois são usados desde os tempos remotos para tratar doenças e promover a saúde em geral. Possuem uma quantidade de compostos bioativos interessantes o que despertou o interesse da área científica. O presente estudo tem como objetivo a avaliação das propriedades bioativas e da composição química e nutricional dos cogumelos Pleurotus sajor-caju e Lentinula edodes. A atividade antioxidante do extrato foi avaliada através de ensaios de DPPH, poder redutor, TBARS e betacaroteno. Foram realizadas atividade antitumoral nas células NCI-H460, HepG2, HeLa, MCF-7 PLP2 HCT-116 e MRC-5, e anti-inflamatória para o extrato etanólico de P. sajor-caju em Raw 264.7. A composição da amostra do P. sajor caju em tocoferóis foi determinada por Cromatografia Líquida de Alta Eficiência (CLAE) acoplada a um detector de arranjo de diodos (DAD). Os perfis em ácidos graxos e açúcares foram obtidos por cromatografia a gas acoplada a um detector de ionização de chama (CG-FID) e por CLAE acoplado a um detector de índice de refração (DIR). O P. sajor-caju mostrou ser fonte importante de antioxidantes principalmente fenóis (147,54 μg/g) e tocoferóis (615.9g/100g). β-tocoferol foi a forma encontrada em maiores quantidades. Este extrato apresentou atividade antioxidante, sendo esta mais significativa para os ensaios de inibição da peroxidação lipídica (valores de EC50 inferiores a 2,6 mg/mL). A determinação do perfil em macronutrientes demonstrou altos teores em proteínas (17,29 g/100 g) e carboidratos (76,18 g/100 g), apresentando baixos valores de lipídios (1,16 g/100 g). A análise da composição do ácidos graxos conduziu à quantificação de 22 moléculas, com predomínio dos ácidos graxos poli-insaturados, particularmente os ácidos oleico e linoleico, 17-61% e 20-54%, respectivamente. O ensaio de citometria de fluxo foi utilizado para a verificação do tipo de morte induzida, para ambos os cogumelos, que apresentaram resultados semelhantes, indicando morte por apoptose. Os estudos efetuados descrevem o potencial nutracêutico das espécies analisadas, bem como o docking molecular nos faz pensar em uma possível atividade pró-apoptótica e anti-inflamatória. O consumo de cogumelos in natura como em extratos podem exercer um efeito benéfico para a saúde e auxiliar no tratamento de determinadas doenças.
Keywords: Cogumelos comestíveis; Apoptose; Cogumelos; Mushrooms, Edible; Apoptosis; Mushrooms